2020
DOI: 10.1186/s12884-020-03091-8
|View full text |Cite
|
Sign up to set email alerts
|

The WOMAN trial: clinical and contextual factors surrounding the deaths of 483 women following post-partum haemorrhage in developing countries

Abstract: Background: Post-partum haemorrhage (PPH) is a leading cause of maternal death worldwide. The WOMAN trial assessed the effects of tranexamic acid (TXA) on death and surgical morbidity in women with PPH. The trial recorded 483 maternal deaths. We report the circumstances of the women who died. Methods: The WOMAN trial recruited 20,060 women with a clinical diagnosis of PPH after a vaginal birth or caesarean section. We randomly allocated women to receive TXA or placebo. When a woman died, we asked participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
2
12
0
3
Order By: Relevance
“…This multicentric WOMAN trial was carried over 6 years and analyzed on narrative data reporting deaths due to PPH. Collaborators of same trial measuring outcome measures as mortality, hysterectomy, and other morbidities in women with clinical post-partum hemorrhage and use of TXA in a placebo-controlled trial report signi cant difference in TXA and placebo group with a p value of 0.045 [19,20,21]. In our study 66% patients did not need any operative intervention and 33% patients needed operative intervention after treatment with TXA.…”
Section: Improvement In Hemoglobin Levelmentioning
confidence: 48%
“…This multicentric WOMAN trial was carried over 6 years and analyzed on narrative data reporting deaths due to PPH. Collaborators of same trial measuring outcome measures as mortality, hysterectomy, and other morbidities in women with clinical post-partum hemorrhage and use of TXA in a placebo-controlled trial report signi cant difference in TXA and placebo group with a p value of 0.045 [19,20,21]. In our study 66% patients did not need any operative intervention and 33% patients needed operative intervention after treatment with TXA.…”
Section: Improvement In Hemoglobin Levelmentioning
confidence: 48%
“…This is comparable to data from the national Ugandan maternal mor- The maternal death notification and review at national level were both at 49% which is the same as our study and considerably less than the annual target of (70%) in Health Sector Development Plan (HSDP) plan 27 . Obstetric haemorrhage is a major cause of maternal death globally 28,29 , but several trials have shown promising results for interventions suitable for implementation in low-resource settings to reduce haemorrhage-related deaths. These include uterotonics such as heat-stable carbetocin 30 , although application in this setting may be limited by cost.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Notably, the study was an abstract – hence we cannot fully evaluate methods and study quality – and the unit cost of tranexamic acid ($187) was significantly higher than other studies ($5.60 to $50.40) which may have affected the findings. The study used data from WOMAN trial, where most (91.6%) of the study participants were from Africa and Asia 28 with higher rates of maternal mortality and more limited health resources compare to the US context.…”
Section: Discussionmentioning
confidence: 99%